Panorama of the investigation of school cyberbullying in Peruvian basic education, decade 2010-2020 - Chalco Fernández, Julio César (2021)
The objective of this bibliometric study is to systematically identify and analyze research on school cyberbullying and education that was carried out in the Peruvian context of the last decade. For this purpose, the methodology used a Document Analysis Sheet with some criteria for the search and analysis of articles (20) and thesis (40) in different databases and repositories. The most important finding is that Peruvian research in relation to school cyberbullying is still incipient compared to the rest of the countries in the region. The highest research output is in theses and is monopolized by a single Peruvian university. The research contexts are especially on the central and north coast. For this reason, we conclude that, although the panorama of research on cyberbullying is still smaller compared to other Latin American countries, the number of works is increasing, especially in the last three years. Keywords: School cyberbullying, Peruvian education, research.